Bimbingan Teknis Pembuatan Biochar Sekam Padi dengan Metode Retort Kiln di Desa Sukadana Lombok Tengah - Zuhdiyah Matienatul Iemaaniah; Lalu Arifin Aria Bakti; Sukartono Sukartono; Siska Ita Selvia; Haidir Ali Salsabil; Jasrodi Jasrodi (Jurnal Pengabdian UNDIKMA, 2023)
This service aims to increase the knowledge and skills of Patuh Bersama farmer group members in processing rice husk Biochar agricultural waste using the Retort Kiln method. The method of implementing this service activity used a technical guidance method with a participatory approach. Evaluation of this activity was carried out through interactive sharing and then the data was analyzed descriptively. The results of this service activity showed that the farmer group could understand and had the skills to make rice husk biochar using the Retort Kiln method. Apart from that, from the results of this service it is hoped that farmers can utilize agricultural waste as a soil improvement material on agricultural land.